Differences in the bird community between a regenerating area and a native forest in Southeastern Brazil - Sementili-Cardoso, Guilherme [UNESP]; Vianna, Renata Marques [UNESP]; Ottonicar, Rafael Gustavo Capinzaiki [UNESP]; Donatelli, Reginaldo Jose [UNESP] (Taylor & Francis Ltd, 2020)
Restoration of degraded areas might be assessed via faunal communities of a particular region, and birds are one of the taxa most suitable in such assessments. This study evaluated the dynamics of a bird community in an area of Cerrado under natural regeneration, comparing it with one in the forest remnants. Birds were censused by a total of 24 point counts in both areas comprising 96 h of total sampling. Richness, abundance and diversity were greater at the regeneration area, possibly due to the heterogeneity of habitats, the consequent niche diversity, and the connectivity between patches of vegetation. Functional groups were also distinct between both sites, including species composition, feeding guilds and foraging strata. The regeneration site presented a higher abundance of omnivorous, granivorous and nectarivorous species, which might be related to the presence of sparser canopy, multiple opportunities for the development of grasses and forest-edge plants blooms in open areas. In contrast, higher abundance of invertebrate predators and frugivorous was found in the forested area, further confirming the relationship between those guilds and dense vegetation cover with closed canopies.
Keywords: Cerrado regeneration; bird communities; forest recovery; functional groups; endangered taxa